Hubungan Dukungan Suami dan Dukungan Orang Tua dengan Efikasi Diri Ibu Menyusui Di Wilayah Kerja Puskesmas Pagaden Barat Kab.Subang - Rokmah, Siti; Rizal, Ahmad; Wahmurti, Tuti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
In everyday life often found mothers who have not managed to breastfeed their babies or even stop breastfeeding their babies early for various reasons. Even the tendency that has occurred lately the number of mothers who do not want to breastfeed their babies is increasing. The most natural way of breastfeeding is by breastfeeding. One of the successes of breastfeeding is increasing maternal self efficacy. In Puskesmas Pagaden Barat Kabupaten Subang the exclusive coverage of breasfeeeding just 38,7% that is 80%. The purposeof this was to analyze the relationship between husband and family support and sel efficacy ofbreasfeeding mother of baby age 0 – 6 months. This study correlation analytic, design that was cross sectional design.the population is the study were primiparous mothers who had babies 0 – 6 month age. The study sample was 92 people,the sampling technique was stratified random sampling. Statistical analysis used chi square and exact fisher. The results of Fisher exact analysis indicate that the support of the husband with self-efficacy with value p = 0.041 while the support of parents with self-efficacy with value p = 1.0. The conclusion of this study is that the husband has a significant (meaningful) relationship with self efficacy, while parental support does not have a meaningful relationship with self-efficacy. His advice is to provide health education about the importance of self-efficacy to pregnant and lactating mothers.